2022
DOI: 10.1002/ccr3.6278
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Complete tracheal obstruction due to mucormycosis: A report of two cases

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, in all these cases, only ten showed tracheal involvement associated with bronchial lesions [4,6]. In 2022, a study reported two more cases of tracheal involvement of mucormycosis [6]. In conclusion, the tracheal location of the infection appears as a rare described condition.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, in all these cases, only ten showed tracheal involvement associated with bronchial lesions [4,6]. In 2022, a study reported two more cases of tracheal involvement of mucormycosis [6]. In conclusion, the tracheal location of the infection appears as a rare described condition.…”
Section: Discussionmentioning
confidence: 84%
“…A systematic review from Ruoxi et al ( 2018) reported sixty cases of mucormycosis in the tracheobronchial tree. Nevertheless, in all these cases, only ten showed tracheal involvement associated with bronchial lesions [4,6]. In 2022, a study reported two more cases of tracheal involvement of mucormycosis [6].…”
Section: Discussionmentioning
confidence: 98%
“…Rhino-cerebral, renal and pulmonary involvement are most commonly seen [ 1 ]. Isolated invasion of the trachea and larynx can lead to life-threatening airway obstruction; however, they are rare manifestations of invasive mucormycosis [ 2 ]. Diagnosis is based on histopathology as culture positivity is uncommon and has poor sensitivity.…”
mentioning
confidence: 99%
“…Imaging findings are present in most cases but not characteristic. For a complete cure, multimodal management is recommended, which includes amphotericin infusions followed by curative resection [ 2 - 6 ]. Conservative management with only amphotericin and bronchoscopic removal of slough has also been reported to be successful [ 7 , 8 ].…”
mentioning
confidence: 99%